Speckle tracking ultrasound as a new tool to predict the weaning outcome of mechanical ventilation patients: a prospective observational study - Li, Rui; Zhou, Yao; Chen, Wan; Lyu, Liwen; Qiu, Guozheng; Pan, Chunxi; Tang, Yutao (Frontiers in Medicine, 2024)
Introduction Speckle tracking ultrasound is a novel technique for evaluating diaphragm movement, yet its guidance in weaning mechanically ventilated patients remains unclear. In this study, we assessed diaphragmatic function using speckle tracking ultrasound and guided the weaning process.Methods: A total of 86 mechanically ventilated patients were included and divided into successful or failed weaning groups. Diaphragmatic function was assessed using speckle tracking ultrasound, M-ultrasound diaphragm excursion (DE), and diaphragmatic twitch force (DTF) after 30 minutes spontaneous breathing trial (SBT). The diagnostic performance of these indicator in predicting weaning outcomes was also evaluated.In this study, a total of 86 patients completed the follow-up for weaning outcomes, with 35 cases of weaning failure and 51 cases of successful weaning. Logistic regression analysis identified whole strain (p=0.037) and DE (p=0.004) as independent predictors of weaning outcome. Receiver operating characteristic (ROC) curve showed that the strain threshold for Costal Diaphragm (Dlcos) was -9.836, Area Under the Curve (AUC) value was 0.760, the predictive specificity for weaning failure was 72.5%, and the sensitivity was 80%. DE value exceeding 1.015 cm had an AUC value of 0.785, noting that DE value had a high specificity (90.2%) for predicting successful weaning, but a lower sensitivity (60%). After merging, the AUC of whole strain and DE was 0.856, and the sensitivity (80%) and specificity (80.4%) were more balanced compared to using DE alone.The findings of this study demonstrate the feasibility of using speckle tracking ultrasound to assess diaphragmatic function in mechanically ventilated patients. The combined utilization of whole strain and DE provides a more precise evaluation of diaphragmatic function in ICU patient, which may improve patient outcome.